KEPENTINGAN TIONGKOK MELAKUKAN DIPLOMASI PUBLIK MELALUI OLIMPIADE BEIJING 2008 - Kasogi, Adnan; ", M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Nowadays, diplomatic activity has increased rapidly along with the increasingly diverse issues in international relations. International relations are no longer seen as relations between countries, but also include international public relations. Thus traditional diplomacy, or what is known as "First track Diplomacy", which only involves the role of government in carrying out diplomatic missions. Of course it will not be effective in order to convey messages of diplomacy to a country. Therefore, public diplomacy activities involving public participation will be needed in order to complement traditional diplomacy activities. China conducted public diplomas to achieve its economic and national interests through the 2008 Summer Olympics in Beijing and Paralympics in 2008. However, various issues in China also affected the interests that China wanted to achieve in the 2008 Beijing Olympics. That through the momentum of the 2008 Summer Olympics in Beijing, China seeks to do its public diplomacy for its economic and national interests and build a positive image of China as an international tourist destination. This effort is made through news management, strategic communications and relationship building through the 2008 Summer Olympics in Beijing.Keywords: Public Diplomacy, China's economic interests, News Management, Strategic Communications, Relationship Building, Beijing 2008 Olympic Games.